“Why Should I Not Speak My Own Language (Chinese) in Public in America?”: Linguistic Racism, Symbolic Violence, and Resistance - Wang, M.; Dovchin, Sender (2022)
This article seeks to understand a Chinese international student's (Hong's) encounters with linguistic racism as symbolic violence as well as why and how he resisted different forms of linguistic racism in different situations. Data findings suggest that linguistic racism as symbolic violence takes different forms through both verbal and nonverbal language under the scrutiny of the white gaze, which produces arbitrary power, control, and domination. This triad of linguistic racism, symbolic violence, and the white gaze formed an intersection, which was practiced through visible and hearable linguistic modalities immediately to subordinate and oppress Hong as a victim. The researchers argue that the triad of linguistic racism, symbolic violence, and the white gaze works hand in glove with each other to construct an intersection, which reproduces and reinforces structures of domination and hierarchy. The researchers, therefore, suggest that more research is needed to deconstruct the complexity and subtlety of the intersection of linguistic racism, symbolic violence, and the white gaze. Educational implications for recognizing and combating linguistic racism are also addressed.